The Influence of Micro Influencers and Brand Trust on Wardah UV Shied Purchasing Decisions on TikTok Among Generation Z in Bandung City - Raya Mojang Ananda; Fitri Lestari (Takaza Innovatix Labs Ltd., 2026)
The development of social media, especially TikTok, has changed the purchasing behavior of Generation Z through the role of micro influencers and the increasing importance of brand trust in marketing skincare products. This study aims to analyze the influence of micro influencers and brand trust on the purchasing decisions of Wardah UV Shield among Generation Z in Bandung City, both partially and simultaneously. The study used a quantitative approach with descriptive and verification methods. The study population was Generation Z consumers in Bandung City who had purchased Wardah UV Shield through TikTok. A sample of 100 respondents was determined using a purposive sampling technique based on the Lemeshow formula. Data were collected through a closed questionnaire with a five-point Likert scale. Data analysis included validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination using IBM SPSS Statistics 26. The results showed that micro influencers had a positive and significant effect on purchasing decisions (β = 0.202; p = 0.025), while brand trust had a stronger positive effect (β = 0.589; p < 0.001). Both variables simultaneously had a significant effect with an R² value of 0.535. The study's conclusion shows that increasing Wardah UV Shield purchasing decisions is more effectively achieved through strengthening brand trust supported by collaboration with credible micro-influencers on TikTok.